Sexuality of women with cervix cancer after treatment: literature review - Nur Afni Sharfina; Ratna Indriawati (Alma Ata University Press, 2021)
Background: Cervical cancer is a complex disease that requires comprehensive treatment from clinical professionals. Treatment of women with cervical cancer, such as radiation, chemotherapy and also surgery (hysterectomy). The positive effect of treatment is that it kills cancer cells. There were also physically negative treatments offered (chemotherapy and radiation), such as vaginal dryness, redness of the vaginal area and vaginal canal. Purpose: This adjustments are linked to sexual function directly. The main objective of this literature review is to finding clinical reports on the sexuality of cervical cancer patients undergoing cervical cancer treatment. This study is a literature review. Data based used are NCBI and Google Schoolar. Methods: This research is a study of literature. NCBI and Google Schoolar are used based on results. The writer uses keywords